Attenuating double jeopardy of negative country of origin effects and latecomer brand. Issue 1 (2014) - ,; ,; ,
<x xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to examine the role of ethnocentrism in attenuating the negative country of origin effect and latecomer brands. The literature has established the importance of the "country of origin" effect, and this study compares consumers in the Asian emerging markets to developed consumers' response to cars from China, India and Russia. Design/methodology/approach – Data on consumers' willingness to purchase cars from emerging markets such as China, India and Russia were collected from 3, 201 respondents in those three emerging markets and in the three most important Western car markets, the USA, the UK and Germany. The study employed a choice‐based conjoint analysis. Findings – The results of this study confirmed the hypothesised ethnocentrism in the emerging markets with a strong preference for their own latecomer brands (Great Wall, Tata and AvtoVAZ, respectively). Developed markets in contrast are more sceptical of the Chinese, Indian and Russian car brands, but there is nonetheless substantial potential, especially with consumers who have previously bought latecomer brands from Asia. Utility values per brand, price, brand‐partnership, product features, warranties and also place of manufacturing/assembly have been calculated in the study. Originality/value – This paper should prove valuable to academic researchers in establishing strong consumer preferences in emerging markets for their own products, and in establishing the potential of latecomer brands in developed markets. <ack> <x xml:space="preserve">Acknowledgements</x> The authors would like to thank the editors and anonymous reviewers for their helpful input. In addition, Roxan Toll (formerly of GMI) is thanked for her early involvement with this project. Global Market Insite Inc. (GMI) and Roxan Toll are acknowledged for their generous and invaluable contribution to the author's data collection, without which this project would not have been possible. </ack>